Demigods on Speedway - Sheehan, Aurelie, 1963- (Book collections on Project MUSE., 2014)
"A collection of linked short stories set in modern-day Tucson, Arizona, featuring characters who struggle to make ends meet, find love, and find meaning in recession-era America. The characters are players in a contemporary southwestern story that draws from tropes and characters in Greek mythology"--